2007
DOI: 10.1007/s11255-006-9173-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of a combination of Sabal and Urtica extract in lower urinary tract symptoms—long-term follow-up of a placebo-controlled, double-blind, multicenter trial

Abstract: In an open-label extension of a randomized, double-blind clinical trial, the long-term efficacy and tolerability of a fixed combination of 160 mg Sabal fruit extract WS 1473 and 120 mg Urtica root extract WS 1031 per capsule (PRO 160/120) were investigated in elderly men with moderate or severe lower urinary tract symptoms (LUTS) caused by benign prostatic hyperplasia (BPH). Two hundred and fifty-seven patients were randomly treated with 2 x 1 capsule/day PRO 160/120 or placebo for 24 weeks, followed by a 24-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 23 publications
1
17
1
Order By: Relevance
“…In a study by Keland, in which a combination of Saba and U. dioica was used compared with finasteride, 3·1 and 4·8 scores of reduction were found in the IPSS scores after 24 and 48 weeks, respectively, showing no significant difference between the experimental and the placebo groups, and inconsistency with our results (Keland, 2000). In Lopatkin et al's study, the consumption of U. dioica and Sabal resulted in an improvement of 50% in the IPSS scores (Lopatkin et al, 2007). In our study, the rate of the improvement in the storage symptoms, proportionate to the increase in U. dioica doses, was higher than the rate in the voiding symptoms.…”
Section: ·31 0·438contrasting
confidence: 84%
See 1 more Smart Citation
“…In a study by Keland, in which a combination of Saba and U. dioica was used compared with finasteride, 3·1 and 4·8 scores of reduction were found in the IPSS scores after 24 and 48 weeks, respectively, showing no significant difference between the experimental and the placebo groups, and inconsistency with our results (Keland, 2000). In Lopatkin et al's study, the consumption of U. dioica and Sabal resulted in an improvement of 50% in the IPSS scores (Lopatkin et al, 2007). In our study, the rate of the improvement in the storage symptoms, proportionate to the increase in U. dioica doses, was higher than the rate in the voiding symptoms.…”
Section: ·31 0·438contrasting
confidence: 84%
“…Benign prostatic hyperplasia (BPH) is one of the most important urological problems that affects the elderly population (Vitalone et al, 2001), and its symptoms are manifested as the lower urinary tract syndrome. This syndrome is manifested as a series of storage and voiding symptoms, and its severity is to such an extent that it affects the patients' daily life and quality of life (Girman et al, 1998;Lopatkin et al, 2007). The storage symptoms are associated with prostatic urethra narrowing, and include delay in starting urination, weak or intermittent urine stream and urine dribbling.…”
Section: Introductionmentioning
confidence: 99%
“…A tea made from the leaves of Urtica pilulifera has traditionally used as a stimulating tonic, blood purifier and hemostatic and for enhancement of hemoglobin concentration (Chrubasik et al, 2007) while the whole plant is a diuretic, antiasthmatic, anti-inflammatory, hypoglycemic, hemostatic, antidandruff and astringent (Delcourt et al, 1996;Abudoleh et al, 2011). In addition, extracts of Urtica pilulifera are useful to relief symptoms of lower urinary tract infection (Lopatkin et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The best described phytotherapeutic agent for prostate disorders was from Serenoa repens (saw palmetto) [[64-68], among others]. Several studies have reported no side effects of saw palmetto treatments [69], and a dietary supplement with S. repens may be effective in controlling prostate cancer tumorigenesis [70].…”
Section: Resultsmentioning
confidence: 99%